The Influence of Drug Availability, Service Quality and Brand Image on Purchase Interest at Wahana Medika Pharmacy - Herawati, Sri Juraenah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study investigates the influence of drug availability, service quality, and brand image on consumer purchase intention at Wahana Medika Pharmacy. Employing a quantitative descriptive method with an explanatory approach, the research involved 295 respondents selected using non-probability sampling. Data was collected via a Likert scale questionnaire distributed through Google Forms and analyzed using multiple linear regression. The results reveal a positive and significant influence of all three independent variables on purchase intention (R² = 0.657). Drug availability (coefficient 0.407), service quality (0.339), and brand image (0.419) individually contribute to increased purchase intention, with brand image exhibiting the strongest effect. The regression model explains 65.7% of the variation in purchase intention, with the remaining variance attributable to factors outside the model. The study concludes that adequate drug availability, excellent service quality, and a strong positive brand image are crucial factors driving consumer purchase intention at pharmacies. Wahana Medika Pharmacy is advised to maintain drug availability, enhance service quality through staff training, and strengthen its brand image through digital marketing strategies and customer loyalty programs. Future research could incorporate additional variables such as price and customer loyalty for a more comprehensive understanding.